A review of current guidelines on pain management for the elderly (老年疼痛相关指南进展) - PENG Xueqing (彭雪清); WANG Pei (王培); QI Xiaojiu (齐晓玖) (Association of Integrative Nursing, 2024)
With the global increase in the aging population, the pain management in elderly patients has becoming a great concern. This paper reviewed the guideline related the pain management for the elderly. The quality and rating of guidelines were evaluated by using AGREE Ⅱ, and the recommendations for pain management care were summarized. It provides a basis for standardizing the pain management in the elderly, so that clinical practitioners can form the pain management guidelines according to the characteristics of the elderly in China. (随着人口老龄化趋势加重, 老年人群的疼痛管理尤为重要。本研究通过对老年人疼痛相关指南的筛查, 使用指南研究与评价工具(AGREEⅡ)进行质量评价、评级, 形成推荐意见的汇总, 旨在为规范老年疼痛管理提供依据, 以及为制定符合我国老年人特点的老年疼痛管理指南提供参考。)